Efficacy Of Penoxsulam Against Weeds In Transplanted Rice (Oryza Sativa L.) Under Temperate Conditions Of Kashmir (Applied Biological Research, 2013)
Field studies were conducted to evaluate the efficacy of penoxsulam against  complex weed flora both as pre- and post-emergence herbicide in transplanted  rice during Kharif seasons of 2008 and 2009 at Mountain Research Centre for  Field Crops, SKUAST-K, Khudwani, Kashmir (India) on a silty clay loam soil  with normal reaction and medium fertility status. Major weed species infesting  the field were Echinochloa crus-galli, Echinochloa colona, Cyperus iria.,  Cyperus difformis, Marsilea quadrifolia, Potamogeton distinctus, Ammania  baccifera and Monochoria vaginalis. The experiment consisted of eight  treatments replicated thrice and laid out in a randomized block design.  Penoxsulum application @ 22.5 g a.i. ha-1as pre-emergence 3-5 days after  transplantation (DAT) provided effective control of almost all types of weed  species thereby resulting in higher paddy yield (72.8 q ha-1) as compared to  weed-free (77.2 q ha-1) and two hand weeding (71.9 q ha-1). Penoxsulam @ 20 g  ai ha-1 was also effective in controlling weeds when applied as post-emergence  (8-12 DAT) and gave a paddy yield of 69.2 q ha-1.
Keywords: Butachlor; herbicides; Kashmir; penoxsulum; rice; weeds